Conversational Implicature in Oprah Winfrey and Meghan Markle’s Interview on thesun.co.uk (A Pragmatic Study) - Ela Martisa; La Aso; Laras Sulistya Ningsih (ELITE: Journal of English Language and Literature, 2022)
This study aims to describe the form of conversational implicature in the Interview between Oprah Winfrey and Meghan Markle. This research is a qualitative descriptive study. The subject of this research is Oprah Winfrey and Meghan Markle. The object of the research is the utterances contained in the Interview between Oprah Winfrey and Meghan Markle. The data was collected through searching, downloading, reading script, note taking, classifying, and coding the data to achieve a complete conclusion in the form of conversational implicature in the interview between Oprah Winfrey and Meghan Markle. The results of the study show three forms, namely satire (6 data), protest (3 data), and statement (14 data). Meghan uses this form because she doesn't want to be silent about the problems she has with the royals who played an active role in perpetuating lies about her and Prince Harry. Â